Return to work after stroke: feasibility six year follow-up - Phillips, Julie (College of Occupational Therapists, 2018)
Background: In a feasibility trial of early occupational therapy vocational rehabilitation (VR), more VR participants were in work at 12 months compared to those who received usual NHS rehabilitation after stroke (UC) (11 [65%] v 6 [35%]) (Radford et al., 2013). However, the longer-term is unknown. Aim: To follow up and explore work status six years post stroke. Method: Postal questionnaires measuring employment, income, mood, functional ability and quality of life (QoL) were sent to participants in an earlier feasibility trial by the lead stroke clinician. Respondents were invited to participate in interviews exploring working six years after stroke. Ethical and HRA approvals obtained (REC 16/EM/0423) Results: Of 48 identified participants, five (10.4%) had died; 19/43 (44.2%) responded. Fourteen were men; mean age 62 (24-78) years. Respondents classified themselves as in paid work 10/19 (53%), voluntary work 3/19 (16%), full time education 1/19 (5%) and solely retired 5/19 (26%). Six respondents were working over the age of 65 (26.3%). Most remained with preinjury employers (11/13). Half (8/15 53%) reported a decrease in income since stroke. Compared to one year, mean functional ability improved marginally from 56.6 (SD 12) to 59.4 (SD 9) but quality of life reduced from mean 77.4 (SD 11) vs 70.7 (SD14). Six interviewees felt working was the correct decision but lacked support with invisible impairments (fatigue, memory) which impacted workability. Conclusion: Work remains important to stroke survivors. Vocational rehabilitation should address hidden disabilities. Response bias may have influenced these findings.